2018
DOI: 10.17770/sie2018vol1.3385
|View full text |Cite
|
Sign up to set email alerts
|

Pursuit of Inclusive Education: Inclusion of Teachers in Inclusive Education

Abstract: By focusing on teachers’ approach, the article analyses one of the most relevant issues of today’s realities of education – the inclusive education. The following is an important task for politicians for education, school leaders, teachers and greatly affects and influences the life of families with children with disabilities. Object of the research: inclusion of teachers in inclusive education. Aim of the research: to examine aspects of teachers’ inclusion in inclusive education by implementing the statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…According to the results of teachers' perception of the effectiveness of solving problems of inclusive education, they lack skills and knowledge for educational adaptation and modification of the educational process in order to support students with special health needs (Monteiro, Kuok, Correia, Forlin & Teixeira, 2018). It is also noted that teachers are insufficiently prepared to help their students with an inclusive curriculum (Baranauskienė & Saveikienė, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the results of teachers' perception of the effectiveness of solving problems of inclusive education, they lack skills and knowledge for educational adaptation and modification of the educational process in order to support students with special health needs (Monteiro, Kuok, Correia, Forlin & Teixeira, 2018). It is also noted that teachers are insufficiently prepared to help their students with an inclusive curriculum (Baranauskienė & Saveikienė, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Malawi, education colleges and some universities train mainstream teachers for primary and secondary education. The NPEOPD strategies can be incorporated into the teacher education curriculum to ensure the inclusion of teachers in inclusive education (Baranauskiene & Saveikiene, 2018). When they teach, mainstream teachers would be mindful of inclusive education and would demonstrate this by preparing effective strategies for supporting learners with disabilities.…”
Section: Legal and Policy Context For Inclusive Education In Malawimentioning
confidence: 99%
“…To recap, inclusive education overwhelms policy development in the broader educational policies worldwide, including in Malawi (Baranauskiene & Saveikiene, 2018;de Beco, 2018). However, Chimwaza's (2015) study found that most of the teachers in Malawi believe that the provision of physical accommodation in the schools guarantees educational success for the learners with physical disabilities.…”
Section: Legal and Policy Context For Inclusive Education In Malawimentioning
confidence: 99%
“…Los contextos educativos, al igual que la sociedad, se caracterizan por su alta heterogeneidad, la cual es considerada como un valor educativo dentro del modelo de educación inclusiva (García Rubio, 2017;Baranauskiene y Saveikiene, 2018). La Organización de las Naciones Unidas para la Educación, la Ciencia y la Cultura (UNESCO) establece entre los diecisiete Objetivos de Desarrollo Sostenible de su Agenda 2030 la necesidad de "Garantizar una educación inclusiva, equitativa y de calidad y promover oportunidades de aprendizaje durante toda la vida para todos" (ODS 4) como base para reducir las desigualdades sociales.…”
Section: Educación Inclusivaunclassified